PERAN MOTIVASI KERJA DALAM MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN PADA PT. MONICA HIJAU LESTARI (THE BODY SHOP) CABANG BLOK M JAKARTA SELATAN - Adella Azizah Prastikasari; Didi Sunardi (Journal of Research and Publication Innovation, 2025)
This research aims to describe and analyze the role of work motivation in increasing employee work productivity at PT Monica Hijau Lestabil (The Body Shop) Blok M branch, South Jakarta. This research uses a qualitative descriptive method with an interpretive approach in analyzing data with a literature review as well as collecting and processing data using observation, interviews, documentation and triangulation. The results of the research show that the role of work motivation in increasing employee work productivity at PT Monica Hijau Severt (The Body Shop) Blok M branch, South Jakarta, cannot still be said to be good, this can be seen from employees who are less motivated in terms of discipline at PT Monica Hijau. Selukis (The Body Shop) Blok M branch, South Jakarta, there is no openness between the company and employees regarding employee problems and a lack of initiative from employees in participating in training/workshops held. However, for this reason, the company will try as hard as possible so that employee work motivation can increase for work productivity at PT Monica Hijau Lestari (The Body Shop) Blok M South Jakarta branch through the rules enforced at PT Monica Hijau Lestari (The Body Shop) branch. Blok M, South Jakarta, hopes that employees will be able to increase their work productivity.